X-ray photoelectron spectroscopy of the MAB phases, MoAlB, M2AlB2 (M = Cr, Fe), Cr3AlB4 and their binary monoborides. Issue 2 (February 2020) - Natu, Varun; Kota, Sankalp S.; Barsoum, Michel W.
Abstract: Interest in the nanolaminated MAB phases, wherein M is a transition metal, A is typically Al, and B is boron, has increased in recent years because some them have attractive properties, such as the high-temperature oxidation resistance of MoAlB or the near room-temperature active magnetic refrigeration capabilities of Fe2 AlB2 . Herein, X-ray photoelectron spectroscopy is used to measure the binding energies (BE) of core electrons in the MAB phases, MoAlB, Cr3 AlB4 and M2 AlB2 (M = Cr, Fe). The BEs of the ternaries were then compared to those of their structurally related binaries, MoB, CrB, and FeB. In all these borides, a large, positive shift in the B 1 s BE relative to that of elemental B was observed. In contrast, the BE shifts of the M and Al atoms were found to be within 0.5 eV of the corresponding pure elements. These results indicate the strong role of covalent and metallic bonding in the MAB phases.